Research progress on climate change adaptation strategies to control invasive crop pest in sub-Saharan Africa: a bibliometric and systematic review - Assèdé, Eméline Sêssi Pélagie; Othoo, Calvince Ouko; Ly, Ahmadou; Bayisa, Gobena; Tarkegn, Temesgen Gashaw; Zohoun, Mègnissè; N’goran, Anje-Jokebed (Frontiers in Climate, 2025)
This bibliometric and systematic review assesses research progress and climate change adaptation strategies to control invasive crop pests in sub-Saharan Africa. Scientific publications on crop pest management in sub-Saharan Africa in a context of climate change adaptation were extracted from papers published between 1991 and 2024. A literature search was conducted on Scopus, dimension, and google scholar, followed by screening and data extraction in compliance with ROSES standards. Findings indicated that pests such as armyworms, fruit flies and coffee berry borer cause huge losses. Communities are adopting integrated pest management, water harvesting, drip irrigation, resistant varieties, and improving production efficiency. Agro-ecological practices reduce pest invasions while preserving the environment. Meanwhile, chemical insecticide use remains an emergency solution as its effects on pest control would be more efficient. However, promising approaches emerge around biocontrol, agroforestry integrating pest management, and gender-tailored strategies. Nevertheless, regional disparities persist in scientific output. In conclusion, while invasive pests represent a major plant health crisis in sub-Saharan Africa, this review highlights innovative adaptation strategies. Their development will require coordinated mobilization to catalyze the sustainable agro-ecological transition that sub-Saharan Africa needs to address these multidimensional challenges. Future research should assess farmer’s perception on the effectiveness of the existing pest management practices for invasive crop pests.